Impact of geometry and magneto-optical properties on field enhancement and optical bistability in core–shell nanoparticles - Tayebeh Naseri; Fatemeh Pourkhavari (Journal of Theoretical and Applied Physics)
Abstract We study the interaction of electromagnetic field with two of the most tunable nanostructure geometries for nanoplasmonics including the magneto-optical nanoshell structure and the spheroidal geometry. We investigate the effect of combining both geometry and magneto-optical properties within the same nanostructure on the field enhancement factor and optical bistability behaviors. Since the coupling between the inner and outer surface plasmons of the nanoshell is stronger for the elongated spheroidal geometry as compared to that for the spherical case, field enhancement in ellipsoid nanoparticles is much more saleintiant. Moreover, the plasmonic field enhancement is four orders of magnitude larger for the spheroidal nanoshells as compared to spherical nanoshells. In addition to the appearance of optical bistability in this system, it is found that the threshold and window of bistability are strongly dependent on magneto-optical properties and geometry of the core–shell nanoparticle.